(untitled) (Journal of Social Sciences Review, 2024)
Pashtunwali, an unwritten tribal code of conduct, has been shaping the lives of millions of Pashtuns, outlining the contours of their socio-cultural hierarchies. This study explores Pashtunwali’s role in creating spatial hierarchies that place Pashtun women at the peripheries of Pashtun spaces, thus making Pashtunwali a patriarchal tool to exert and maintain spatial dominance of Pashtun patriarchy. Using theoretical underpinnings of spatial theory as propounded by Tim Cresswell, Edward Casey, and David Sibley, this study explores Pashtun women’s spatial experiences of in-placeness, out-of-placeness, and transgression within the normative geography constructed through Pashtunwali. The study offers a critique of the Pashtunwali to comprehend how it creates spaces of exclusion for Pashtun women and hampers their leadership within the Pashtun society. The current research concludes that Pashtunwali creates an ambivalent normative geography where Pashtun women experience being out of place and excluded from leadership spaces.